Endogenous Determinants Influencing Financial Performance Of Manufacturing Industry: Evidence From Pakistan - Dr. Muhmmad Rizwan Kamran , Aftab Hussain Tabasam , Fahad Saeed , Ms Sadaf Ambreen , Kinat Bibi , Ch Kamran Mahmood (Migration Letters, 2024)
The current study examines the Endogenous factors on the profitability of manufacturing companies in Pakistan. The data was selected from the State Bank of Pakistan website. The data set used for this study is the panel data from 2014-2023. The most suitable regression analysis models—the pooled OLS model, the fixed-effect model, and the random effect model—have been applied to examine the effect. Out of the two models, the Breush-Pagan Lagrange Multiplier (LM) and Hausman test were used to determine which model was the best fit. Based on test findings, the Random effect model is the most suitable model for the current study. The results demonstrate that while leverage has a strong and adverse relationship with ROA, all internal variables, such as Tangibility efficiency and effectiveness, have a positive and significant impact on the profitability of the manufacturing sector of Pakistan. Moreover, the size of the firm is insignificant in relation to profitability. It is recommended that the debt portion should be declined to enhance the manufacturing sector’s profitability.